Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch83
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterisation of High Temperature Oxidation of Nickel Base Superalloy RR1000 and the Effect of Shot‐Peening

Abstract: High temperature oxidation resistance is becoming increasingly important to component life as operating temperatures increase. Additionally, shot-peening is used to help extend the service life of high-duty components through inducing compressive stresses in the surface. The effect of shot-peening on oxidation resistance has not been examined in detail, at least on recent high-strength turbine disc alloys such as RR1000. In this study, oxidation of a coarse-grained variant of RR1000, with and without shot peen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…However, shot peening has also been shown to increase oxidation rates in alloys where protective oxide scales are normally found. This is the case in previous work investigating the weight gain kinetics of RR1000 where it was shown that shot-peening had an adverse effect on oxidation at 700 and 750 o C [17].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, shot peening has also been shown to increase oxidation rates in alloys where protective oxide scales are normally found. This is the case in previous work investigating the weight gain kinetics of RR1000 where it was shown that shot-peening had an adverse effect on oxidation at 700 and 750 o C [17].…”
Section: Introductionmentioning
confidence: 80%
“…The work complements an earlier study [11] on the un-peened RR1000 alloy and detailed comparison with these earlier data will be made in the present work. The earlier work conducted on this alloy by the same authors recorded the mass-gain oxidation kinetics [9,11,17], sub-surface oxidation kinetics [10]. As part of the detailed investigation performed the presence of Ti within the chromia was noted [11].…”
Section: Introductionmentioning
confidence: 96%
“…The surface condition of the alloy plays an important role in its resistance against oxidationinduced damage. 4,5 Shot-peening is a widely used surface treatment primarily sought for its ability to offset high mechanical loads at the surface, but shotpeening effects could be both beneficial and detrimental to an alloy's long-term integrity because the process itself imposes high levels of surface and subsurface deformation.…”
Section: Introductionmentioning
confidence: 99%
“…3) identifies these intrusions as alumina, in agreement with earlier work on similar and related alloys. [2][3]5 It is also worth noting that the interface between the oxide scale and the underlying alloy is similar between the two preparation and imaging methods and shows no evidence of cracking. In both preparation techniques, small voids were present in the outer oxide.…”
Section: Resultsmentioning
confidence: 88%
“…Such intrusions are features of pure ternary alloy systems, 1 as well as advanced Ni based superalloys. [1][2][3][4][5] Recently, however, it has been claimed 6-8 that subsurface voids occur as a consequence of oxidation and these may or may not be associated with alumina intrusions (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%